2018
DOI: 10.1002/bmb.21159
|View full text |Cite
|
Sign up to set email alerts
|

Physical models can provide superior learning opportunities beyond the benefits of active engagements

Abstract: The essence of molecular biology education lies in understanding of gene expression, with subtopics including the central dogma processes, such as transcription and translation. While these concepts are core to the discipline, they are also notoriously difficult for students to learn, probably because they cannot be directly observed. While nearly all active learning strategies have been shown to improve learning compared with passive lectures, little has been done to compare different types of active learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
3
28
0
1
Order By: Relevance
“…The similar accuracies of eyesight and oral or manual sensing of models suggest that tiny models will be useful to students without visual impairments, as these students benefit from active learning with 3D models ( 58 ). The perception of ambiguous shapes (and confidence in perception) can be greater by manual tactile sensing than by eyesight ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…The similar accuracies of eyesight and oral or manual sensing of models suggest that tiny models will be useful to students without visual impairments, as these students benefit from active learning with 3D models ( 58 ). The perception of ambiguous shapes (and confidence in perception) can be greater by manual tactile sensing than by eyesight ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that visuo-semiotic models, such as physical molecular models, can enhance learning. For example, Newman et al (2018) showed that physical molecular models could improve student learning because they engage various receptor sense organs through which information is internalized. This includes internalizing information through visual perception, aural perception, as well as haptic perception.…”
Section: The Role Of Visuo-semiotic Models In Learningmentioning
confidence: 99%
“…Some examples are the usage of 3D-printed protein models, transcription and translation models, colorimetric enzymatic reactions, or computer-based simulations. [1][2][3][4][5][6] A typical introductory biochemistry laboratory course likely includes experiments in enzyme expression, purification, and characterization. Visual cues and observation may be critical for these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a visual component to a classroom or lab exercise has been shown to increase learning in a number of studies. Some examples are the usage of 3D‐printed protein models, transcription and translation models, colorimetric enzymatic reactions, or computer‐based simulations 1–6 . A typical introductory biochemistry laboratory course likely includes experiments in enzyme expression, purification, and characterization.…”
Section: Introductionmentioning
confidence: 99%